2022
DOI: 10.3389/fimmu.2022.894707
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future: The Relationship Between Circular RNA and Immunity

Abstract: The immune system has evolved since the birth of humans. However, immune-related diseases have not yet been overcome due to the lack of expected indicators and targeting specificity of current medical technology, subjecting patients to very uncomfortable physical and mental experiences and high medical costs. Therefore, the requirements for treatments with higher specificity and indicative ability are raised. Fortunately, the discovery of and continuous research investigating circular RNAs (circRNAs) represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 168 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…CircRNAs are involved in the pathogenesis of immune-related diseases such as autoimmune diseases, cancer, and infectious diseases ( 131 133 ). Many studies have indicated that circRNAs play critical roles in immune responses, particularly in cells in myeloid and lymphoid lineages ( 100 , 134 ).…”
Section: Roles Of Circrnas In Ibdmentioning
confidence: 99%
“…CircRNAs are involved in the pathogenesis of immune-related diseases such as autoimmune diseases, cancer, and infectious diseases ( 131 133 ). Many studies have indicated that circRNAs play critical roles in immune responses, particularly in cells in myeloid and lymphoid lineages ( 100 , 134 ).…”
Section: Roles Of Circrnas In Ibdmentioning
confidence: 99%